The Agreement between the Conventional and Digital Radiographs in Detection of Intracanal Separated Files - Anosha Memon, Kelash Kumar, Mubariz Ahmed Humayun, Israa Ahmed, Shakaib Ahmed, Jamshidullah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: to determine the agreement between the conventional and digital radiographs in detection of intra canal separated files. Material & Methods: A cross sectional study was conducted at Operative Dentistry Department, Institute of Dentistry, Liaquat University of Medical and Health Sciences, Jamshoro from 01-03-2020 to 31-08-2020. A total of 71 Permanent single straight rooted, consisting of single canal extracted teeth were included in this study. Preoperatively radiograph was taken from mesiodistal (M-D) and buccolingual (B-L) direction to confirm the inclusion criteria. Root canal was prepared and the file was inserted to the working length, a counterclockwise motion was performed till the separation of file occurs. Then radiograph was taken to confirm the separated file at working length. Results: Agreement between the conventional and digital radiographs in detection of intra canal separated files was 90.4%. The kappa value between the conventional and digital radiographs was 0.534 which is statistically significant and considered as a moderate degree of agreement. Practical Implication: Correct radiographic detection helps identify the cause, improves in therapy choice, and offers medico legal security in cases of retreatment. Conclusion: In conclusion, both modalities can be used for detection and facilitate in finding the cause and helps in decision making for treatment and provides medico legal security in the retreatment cases. Keywords: Conventional radiograph, Digital Radiographs, Endodontic treatment, Separated file.